Beispiel Nr: 13
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(\frac{1}{2}/0)\qquad Q(-2/0) \\\\ \\ \textbf{Rechnung:} \\ P(\frac{1}{2}/0)\qquad Q(-2/0) \qquad a=1\frac{1}{2} \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=1\frac{1}{2}(x-\frac{1}{2})(x+2)\\ y=1\frac{1}{2}(x^2- x \cdot \left(-2\right) -\frac{1}{2}\cdot x +\frac{1}{2}\cdot \left(-2\right) )\\ y=1\frac{1}{2}(x^2 +1\frac{1}{2} x-1) \\ y= 1\frac{1}{2}x^2-2\frac{1}{4}x-1\frac{1}{2} $